RETRACTED: Innovative approaches to strategic management of analytical studies and forecasting of the activities of hotel and restaurant business enterprises - Dzhyndzhoian Volodymyr; Khodak Olga; Yakovlieva-Melnyk Nataliia (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 538, 00001 (2024), https://doi.org/10.1051/e3sconf/202453800001